PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, DAN LEVERAGE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN DI BEI PERIODE 2019-2021 - Stevani Widowati; Ahmad Husin; Santosa Tri Prabawa (STIE Wijaya Mulya, 2025)
The purpose of this study was to determine the effect of company size, liquidity, and leverage on financial performance in food and beverage sub-sector companies on the Indonesia Stock Exchange (IDX) for the period 2019 â€“ 2021. This type of research uses quantitative descriptive analysis. The sampling method uses a purposive sampling method. Based on predetermined criteria, a sample of 14 companies in the food and beverage sub-sector was obtained. The analysis technique used is classical assumption testing, multiple linear regression analysis, hypothesis testing using the SPSS application. The results of the research show that the t test calculation (partial) shows that company size has a significance value of 0.025<0.05. Liquidity has a significance value of 0.001<0.05 leverage has a significance value of 0.299>0.05. Meanwhile, the results of the F test calculation (simultaneous) show a significance value of 0.003â‰¤0.05. Based on the test results, it can be concluded that company size partially affects financial performance, liquidity partially affects financial performance, and leverage partially does not affect financial performance. Meanwhile, simultaneously between firm size, liquidity, leverage have an influence on financial performance.Â Keywords : Company Size, Liquidity, Leverage, Financial Performance